Water Inrush Mechanism of Karst Collapse Column in Coal Seam Floor Based on a Variable Mass Seepage Mechanical Model. (25th July 2022) - Feng, Yang; Hai-xiao, Lin; Ling-yan, Shen; An-zhi, Yan; Yong-jiang, Wu
Abstract : Water inrush of collapse column in the coal seam floor in the karst area is a frequent hydrogeological disaster, and it is becoming one of the significant hidden dangers threatening the safety of coal mine production in China. Based on the self-developed variable mass seepage test system of broken rock mass, different Talbot gradation seepage tests are carried out in the laboratory. A three-flow field coupled nonlinear seepage model is established based on the variable mass seepage theory and fluid mechanics theory of fractured rock mass. The three flow fields are Darcy laminar flow in the aquifer, variable mass seepage in the collapse column, and Navier-Stokes turbulent flow in the roadway. Combined with a project, a numerical calculation model is established to study the water-conducting channel's formation process and the fluid flow pattern change. The research achievements indicate that the pore pressure gradient and seepage velocity are both 95% fit with the Forchheimer equation, and the seepage of the broken rock mass conforms to the Forchheimer equation. The seepage and migration of particles caused changes in pressure and flow rate, the pressure at the boundary between the aquifer and the collapse column decreased by 0.26 MPa, and the flow rate increased from 0.01 mm/s to 0.064 mm/s. The formation of the water-conducting channel can be divided into two stages, the seepage channel stage and the water-conducting channel stage. The initial fractures continue to develop with the seepage and migration of particles until the water-conducting channel is formed. At the bottom of the collapse column, the Forchheimer number increases from 0.72 to more than 1, and the flow changes from laminar flow to nonlinear seepage. The Forchheimer number at the center of the collapse column fluctuates between 7.5 and 55 at the top of the collapse column. The research results can be treated as an essential basis and reference for the water inrush control of the collapse column and the reasonable prediction of the water inrush amount.